Relationship Between Tectonic Evolutions and Presence of Heavy Oil in The Central Sumatra Basin - Herru Lastiadi Setiawan; Suliantara Suliantara; Bambang Widarsono (Scientific Contributions Oil and Gas, 2021)
Heavy oil is formed through biodegradation process of hydrocarbons, as well as water washing, in which light hydrocarbon fraction disappears and leaves the heavy fraction. Heavy oil is essentially an asphaltic, dense (low API gravity), and viscous that is chemically characterized by its high content of asphaltenes in the oil. Although variously defi ned, 25o API is set the upper limit for heavy oil. Heavy oil in the Central Sumatra Basin is evidently formed as a result of biodegradation and water washing (a hydrodynamic process within oil reservoir) mechanisms. These processes occur as result of tectonic uplift of the reservoir after it has been fi lled with hydrocarbons. Heavy oil reservoir depths in the Central Sumatra Basin are generally shallower than 1,000 feet (300-400 meters), at which surface water may may be associated with the reservoir hence enabling the heavy oil transformation. A combined geology, remote sensing/geographic information system ( GIS), geophysics, stratigraphy, and wellbased analyses is utilized to serve the study. It has been observed that within the northern part of the basin, heavy oil is mainly found in fi elds located within uphill fault blocks such as the up-thrown part of the Sebanga thrust fault with its Duri, Sebanga North, Kulin, Rantau Bais, Batang, Akar, and Genting fi elds. In the western part of the basin there are the Kumis, Kotalama and Pendalian heavy oil fi elds associated with Dalu-Dalu thrust fault and Gadang Island uplift. In total 51 fi elds/structures containing or suspected to contain heavy oil are associated with uplifted geological positions, hence showing the strong relations between tectonic evolutions and present day presence of heavy oil within the basin.